Epigallocatechin gallate inhibits Francisella tularensis growth and suppresses the function of DNA-binding protein HU. (March 2023) - Pavlik, Pavla; Jost, Petr; Rehulka, Pavel; Vozandychova, Vera; Link, Marek; Spidlova, Petra
Abstract: Francisella tularensis is a highly infectious intracellular bacterium causing tularemia disease and is regarded as a potential biological weapon. The development of a vaccine, effective treatment, or prophylactic substances targeted against tularemia is in the forefront of interest and could help to prevent or mitigate possible malevolent acts by bioterrorism utilizing F. tularensis . The viability of F. tularensis, and thus of a tularemia disease outbreak, might potentially be suppressed by simple commonly available natural substances. Epigallocatechin gallate (EGCG) is contained in green tea and its antimicrobial effect has been described. Here, we show that EGCG can suppress F. tularensis growth and is able to reduce the bacterium's ability to replicate inside mouse bone marrow-derived macrophages (BMMs) without side effects on BMMs' own viability. We suggest one (but not the only) mechanism of EGCG action. We demonstrate that EGCG can block the main functions of HU protein, the important regulator of F. tularensis virulence, leading to overall attenuation of F. tularensis viability. EGCG can delay death of mice infected by F. tularensis and can be used as a prophylactic agent against tularemia disease. Postponing death by up to 2 days can provide sufficient opportunity to administer another treatment agent. Highlights: Francisella tularensis constitutes risk as a potential biological weapon. Therefore, a vaccine, therapies, and prophylaxes are much needed. Contained in green tea, epigallocatechin gallate (EGCG) has antimicrobial effects. EGCG can suppress F. tularensis growth and reduce its replication in macrophages. Functions of F. tularensis virulence regulator HU protein can be blocked by EGCG.